Gledališče zatiranih kot oblika artivističnega gledališča v Sloveniji - Polajnar, Barbara (Amfiteater (Ljubljana), 2020)
The Theatre of the Oppressed is an arrangement of theatre techniques representing a place to talk about topics otherwise not addressed and giving voice to the people who otherwise remain unheard. Attributed to Brazilian director, writer and politician Augusto Boal, its beginnings date back to the 1950s. In Slovenia, the Theatre of the Oppressed has been continuously and thoroughly present from 2010 through workshops, educational modules, theatre plays and festivals. In this article, the author presents three examples of good practices from Slovenia that are adapting and developing this method of artivistic theatre for the Slovenian audience. The first two examples focus on the development of new practices of the Theatre of the Oppressed in KUD Transformator, namely ImproForum and the project for children My Fairytales and Rights . The third example is the international project Resilient Revolt, which addresses environmental and climate change issues through the method and multiplication of the produced performance, developed with international partners in their respective countries.
Keywords: artivism; artivizem; community; družbene spremembe; gledališče zatiranih; political theatre; politično gledališče; sistemsko zatiranje; skupnost; social changes; systemic oppression; Theatre of the Oppressed